Magnetic and magnetocaloric properties of LaCr1-xMnxO3 (x = 0, 0.05, 0.1). Issue 17 (1st December 2019) - Biswal, Hrudananda; Singh, Vikram; Nath, R.; Angappane, S.; Sahu, Jyoti Ranjan
Abstract: Magnetic and magnetocaloric properties of LaCr1-x Mnx O3 (x = 0, 0.05, 0.1) synthesized by solid state reaction have been investigated. They exhibit PM to CAFM transition with Néel temperature (TN ) and paramagnetic Curie-Weiss temperature (θ) undergoing shift towards lower temperature upon increasing concentration of Mn. Significant enhancement in value of magnetisation has also been noticed due to development of ferromagnetic nature which is corroborated in hysteresis measurement where loops are observed upon substitution of Mn. Arrott plots confirm the magnetic transition as second order. MCE is observed for all the compounds with maximum value of change in entropy, − Δ S M max, falling in the range of near-room-temperature region. − Δ S M ∼ T curves were seen to peak at TN which register rise as a function of applied fields. Relative cooling power (RCP) were calculated for all the compositions. It was found to increase with fields applied with value of RCP recorded, for example, for x = 0.1 equal to 1.81 J/Kg at 9 T.